Big Eden [videorecording (DVD)] - Bezucha, Thomas; Gross, Arye; Fletcher, Louise; Schweig, Eric, 1967- (Wolfe Video, 2002)
A successful but lonely New York artist returns to Montana after years away to care for his ailing grandfather and discovers new possibilities for friendship and romance.